Metabolomics study of cerebrospinal fluid from diabetic rats with cognitive impairment simultaneously treated with Panax quinquefolius and Acorus gramineus. (27th January 2021) - Yang, Yang; Wang, Dongxue; Zhao, Ying; Wang, Yue; Bi, Yuying; Bi, Tiantian
Abstract: A metabolomics approach was used to explore the effects of Panax quinquefolius (PQ) and Acorus gramineus (AG) on learning and memory in rats with diabetic‐induced cognitive impairment. Thirty Wistar rats were divided into three groups, namely, the normal group, model group, and PQ–AG group (PQ–AG group, 1.80 g/kg/d). Diabetes was induced by intraperitoneal injection of streptozotocin (65 mg/kg). Cerebrospinal fluid (CSF) was collected via cisterna magna puncture, and the Morris water maze method was used to evaluate learning and memory in rats after 11 weeks of PQ–AG treatment. Metabolic profiling of CSF samples was performed by using UPLC–Q‐TOF–MS. Compared with the normal group, the escape latency of the Morris water maze was significantly prolonged in model group rats after 12 weeks ( p < 0.01). Compared with the model group, however, the escape latency was significantly shortened in PQ–AG group rats ( p < 0.05). In multivariate statistical analysis, we identified 33 potential biomarkers, and six biomarkers were altered by PQ–AG. These biomarkers were involved in the metabolism of pyrimidine; nicotinate, and nicotinamide; glycine, serine, and threonine; and ascorbate and aldarate. Taken collectively, our results indicate that PQ–AG can attenuate diabetic‐induced cognitive impairment by affecting a variety of metabolic pathways. Our results provide an experimental basis for studying the mechanism of action of PQ–AG.